Home bias, transactions costs, and prospects for the Euro: A more detailed analysis - Catherine L. Mann; Ellen E. Meade (Deutsche Bank Research, 2002)
This paper brings together the literature on determination of home bias in equity holdings and the portfolio balance model of exchange rates to consider whether the dollar might be affected by a change in transactions costs that alters international portfolio allocations. The empirical findings lend support to the view that transactions costs have a significant influence on US portfolio holdings, even after accounting for float market share. In addition, new survey evidence on the equity holdings of European firms indicates home bias for European investors, and points to a reduction in the magnitude of this home bias since 1997.
Keywords: F21; F31; G11; G15; 330; portfolio choice; equity flows; exchange rates; Portfolio-Investition; Währungswettbewerb; Wechselkurs; USA; EU-Staaten; Home Bias Puzzle